Design of a Web-Based Learning Management System for Physics Education FKIP University of Riau - Salsabilla Azahra Putri; Feri Candra (Jurnal Inovtek Polbeng Seri Informatika, 2023)
21st-century technology requires everyone to see and continue to advance in learning in various forms. Technology is a reference in the success of the learning process supported by the quality of teaching, teaching staff, and curriculum. The Physics Education Study Program at the University of Riau in its learning still uses conventional methods. Learning is only carried out by students and lecturers in class in a short time so students often do not understand the material provided. Based on these problems, we need a learning management system. The goal is to add a limited amount and short meeting time. The system was built using the PHP and MySQL programming languages with the CodeIgniter framework. This study uses the Research and Development (R&D) method and software development uses the System Development Life Circle (SDLC) method with a variation of the v-model. Based on software testing using a black box, all features run 100% well and the User Experience Questionnaire (UEQ) test found that the Learning Management System has good appeal, clarity, and certainty. While efficiency is categorized as very good, stimulation and novelty are included as above average.